Health seeking behaviour of women with unwanted pregnancies: a tertiary care centre based study of eastern Uttar Pradesh, India - Gupta, Sudhir Kumar; Tiwari, Harish Chandra; Srivastav, Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Termination of an unwanted pregnancy is legal in India. Many women in this region are still not aware about safe abortion services and its consequences. Especially young, economically deprived and those without a supportive male partner are at higher risk of unsafe abortion. There is no clear and established evidence on this issue in our region. In the study, the aim was to explore the health seeking behaviour of women with unwanted pregnancies. Methods: Present cross-sectional study was conducted among 303 patients visiting to obstetrics and gynecology ward of BRD Medical College, Gorakhpur from April 2018 to September 2018. Their socio demographic profile, reasons for current termination of pregnancy and health seeking behaviour was explored. Results: Most common reason given for terminating the current pregnancy was completed family size 65.3%. Unmarried girls with pregnancy were 5.6 % who wanted termination of pregnancy. Majority (67.0%) took medication for termination of pregnancy from nearby medical store without an expert consultation 15.8% of women consulted to a local quack or local dai for termination of pregnancy. 12.9% of women tried a method as advised by family/friends for termination of pregnancy. About 4% of women 1st tried traditional and herbal medicines, drinking tea or juice for termination of pregnancy. Majority of women (84.5%) visited to medical college for management of complications of earlier tried method of termination of pregnancy. Conclusions: Completed family size was found most common reason for termination of pregnancy. Self medication without consultation of authorised doctor was found most common practice of abortion leading to complications.